CARACTERIZAÇÃO DAS TIPOLOGIAS DE JANELAS EM EDIFICAÇÕES COMERCIAIS: VITÓRIA/ES - Ghidetti, Bianca; Rodrigues, Edna; Hülle, Laryssa (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Windows are considered qualifying elements of the physical structure of a building and play a fundamental role in the renovation of indoor air, allowing the use of natural ventilation. With the growth of the construction sector, followed by the emergence of modern technologies, the windows have undergone changes in their use and models, thus varying the materials, shading devices, opening system, dimensions and location. Therefore, the objective of this research was to identify and characterize the types of windows used in commercial buildings, located in the neighborhoods with potential real estate investment in the city of Vitória - ES. For this, the following methodological steps were used: definition of the area; field survey; analysis of data obtained and characterization of the observed windows. The field survey used as an auxiliary tool a table of typologies of windows, containing the model and physical characteristics. As a result, a diversity of windows that vary in the model and materials was obtained. In addition, it was possible to highlight that the window typology is determinant for its usability, as well as the adequacy of air movement and thermal comfort levels, it also contributes to the reduction of energy consumption in commercial buildings.